Reflection of the Implementation of the Soviet Health System in the Complaints of the Inhabitants (1944–1953) - Vaiseta, Tomas (Genocidas ir rezistencija, 2015)
The subject of the article is health care. The development of a universal free health care system from the beginning of the Soviet occupation had to become, in conjunction with other social programmes, one of the cornerstones of the Sovietisation tools: on the one hand, these programmes made the whole population directly dependent on the benevolence of the state, on the other hand, it cannot be denied that free and “universally accessible” services helped the Soviet regime earn favour with many inhabitants. We could claim that industry based on industrialisation plans was the backbone of the Soviet regime, while the health care and social security systems were like the nervous systems branching out from the backbone and covering the whole of society. This article aims to examine how the implementation of the Soviet health care system in the first and most ruthless years of the occupation (1944–1953) looked from the bottom (how it was understood by the inhabitants and what problems they saw) and what this says about the Sovietisation process in this area. In order to examine this, the complaints of inhabitants sent to the Ministry of Health of the Lithuanian SSR will be studied, because it is from these complaints that we can learn not only about the control mechanism of the regime and the involvement of ordinary citizens in it, but also about some aspects of the daily life of ordinary residents.
Keywords: Lithuania; Soviet health system; stalinist period